Portraits of Women's Paid Domestic-Care Labour: Ethnographic Studies from Globalizing India. (August 2018) - Grover, Shalini; Chambers, Thomas; Jeffery, Patricia
Our introduction to this Special Issue draws out themes from all four articles which focus on India's domestic-care economy: women's paid domestic labour, care work and surrogacy. Through fine-grained ethnographic detail, all the articles nuance questions around agency and resistance, and actively challenge the 'passive victim' stereotype that continues to be the primary imaginary in many representations of domestic-care workers. We describe how the articles detail the intimacy, emotional labour and complex spatial dynamics inherent within a sector that often involves working in the homes of others, caring for children, and complex relationships with employers. Additionally, we show how care workers encounter quotidian forms of bodily control, distancing, segregation, authority, stigma, coercion, punitive sanctions and exploitation embedded in the intersections of class, race, caste, gender and ethnicity. To provide a wider framing for the articles, we utilize this introduction to situate them within broader historical and geographical contexts. Thus, we consider how global care chains (GCCs), labour markets, migration, and colonial/postcolonial considerations interplay in shaping the everyday lives of domestic-care workers in contemporary globalizing India.